Réponses

2013-08-06T10:53:45+02:00

   A  =  (x + 1)² − (3x − 1) (x + 1)
       =  (x + 1) (x + 1) − (3x − 1) (x + 1)
       =  (x + 1) [ (x +1) − (3x − 1) ]
       =  (x + 1) (x + 1 − 3x + 1)
       =  (x + 1) (−2x + 2)

 

   B  =  9x² − 12x + 4
       =  (3x)² − 2(3x)(2) + (2)²
       =  (3x − 2)²                                                  car   a² − 2ab + b²  =  (a − b)²

 

   C  =  (3x − 8)² − 121
        =  (3x − 8)² − (11)²
        =  (3x − 8 + 11) (3x − 8 − 11)                      car   a² − b²  =  (a + b) (a − b)
        =  (3x − 3) (3x − 19)

 

   D  =  49x² + 14x + 1
       =  (7x)² + 2(7x)(1) + 1²
       =  (7x + 1)²                                                 car   a² + 2ab + b²  =  (a + b)²